#30: Patterns of Post-Exposure Prophylaxis for Varicella-Zoster Virus in Pediatric Patients. (26th March 2021) - Sun, Shan; Patel, Sameer; Jhaveri, Ravi
Abstract: Background: Varicella-Zoster virus (VZV) is still a significant threat for severe illness for patients in high-risk groups. These patients are candidates for post-exposure prophylaxis (PEP), but among adult providers there is significant variation on what agents are used for PEP. There are little data on PEP practices among pediatric providers. Objective: We sought to define patterns of PEP for VZV exposure across children's hospitals. Methods: Using the Pediatric Health Information Systems database, we analyzed claims data for the relevant ICD-9/10 codes for VZV exposure from 2009 to 2018. We evaluated patients for subsequent VZV disease, and we also evaluated how frequently PEP was given, how many days after the exposure or admission, and what agent was used for PEP. We analyzed annual data and institutional-level data over the study period and looked for trends over time. We performed Kruskal–Willis testing when comparing more than two independent samples of equal or different sample sizes. Results: Over the 10 years, we identified 1726 children with VZV exposure, 1622 of them with only one exposure. Of these 1662 children, 683 (42.1%) were prescribed some form of PEP after VZV exposure, while 75 (4.6%) ultimately developed some form of symptomatic VZV. Among the agents used for VZV PEP, acyclovir along was the most frequently used overall, but its use declined over time (45% in 2009 to 30% in 2018). Immunoglobulin was the second most used option (26–43%), while a consistent percentage (4–19%) of children also received the combination of acyclovir and IG. Varicella-specific immune globulin (VariZIG) was used sparingly before 2013, but its use was more frequent from 2015 to 2018 (23–27%). Most children receiving VZV PEP had some form of malignancy, with various newborn populations comprising most of the rest of PEP recipients. Efficacy in preventing VZV was significantly different: 27/218 (12.4%) of children with acyclovir PEP ultimately had a VZV-diagnosis code, compared with 1/148 (0.7%) and 1/112 (0.9%) treated, respectively, with either IG or VariZIG (P < 0.0001). Conclusions: Increasing use of VariZIG likely corresponded to widespread US availability after a long market absence. Nonetheless, the management of VZV PEP in children with high-risk conditions varied considerably across institutions. As the CDC and AAP Red Book list VariZIG as the primary option for PEP, there is considerable room to optimize PEP practice and reduce breakthrough VZV infections.